KEPENTINGAN TIONGKOK DALAM MENGEMBANGKAN PARIWISATA TIBET MELALUI TIBET TOURISM MASTER PLAN 2005 – 2014 - Wardana, Jolyn Andrea; Priadarsiny, Ni Wayan Rainy; Kawitri Resen, Putu Titah (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT This research aimed to find out China's interests behind the Tibet Tourism Master Plan policy. Data was obtained through library methods such as books, scientific journals, e-books, official state documents, and related websites. Afterwards the collected data is described with descriptive qualitative method, which means the answer to research questions is explained in form of words rather than numeric. Research analysis used the concept of internal colonialism and national interests. The concept of internal colonialism helped explain the process of changing the Tibetan region into a Chinese colony and the concept of national interest analyzed China's interests behind the policy of the Tibet Tourism Master Plan. Both of these concepts have a correlation, China conditions Tibet as a colony because there are several interests that need to be achieved. The result obtained was that there are economic and hegemony interests that China wants to achieve in developing tourism in Tibet. Keywords: Chinese Occupation, Tibet Tourism Master Plan, Internal Colonialism, National Interest